Digital Classrooms: The Impact of Virtual and Augmented Reality on Education - Algarhy, Mohammad Hasan (Journal of Research in Vocational Education, 2025)
The integration of Virtual Reality (VR) and Augmented Reality (AR) in education is transforming the traditional classroom, offering immersive and interactive learning experiences that enhance student engagement and comprehension. This paper investigates the impact of VR and AR on education, highlighting their ability to create dynamic, experiential learning environments that support the visualization of complex concepts, foster active participation, and cater to diverse learning styles. VR enables learners to engage with simulated environments, such as historical reconstructions or virtual laboratories, making abstract or distant concepts more accessible and experiential. AR, by overlaying digital content onto the real world, provides immediate, contextualized information, enriching the physical learning environment with interactive elements. Together, these technologies not only deepen understanding but also promote motivation, critical thinking, and collaboration in the classroom. While the potential of VR and AR is vast, this paper also addresses the challenges of their implementation, including high costs, technical barriers, and issues of accessibility. These obstacles present significant limitations to widespread adoption, particularly in under-resourced educational settings. Nonetheless, the ongoing advancements in VR and AR technology, coupled with growing evidence of their educational benefits, indicate a promising future for their role in shaping modern pedagogy. This paper advocates for increased research, investment, and policy support to overcome these barriers and realize the full potential of VR and AR in education. By leveraging these technologies, educators can create more engaging, personalized, and effective learning environments, ultimately enhancing educational outcomes and preparing students for the demands of the 21st century.